PERCEIVED BENEFITS OF ACCOUNTING RECORD KEEPING ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN ABA - ROSELINE CHINASA AGBARAEVOH; ACHARA LARRY OGOCHUKWU (International Studies Journal, 2025)
This study adds to the existing research on SME financial management by analysing the relationship between accounting practises, their perceived benefits and how widely they are used and their impact on performance. While studies have consistently stressed how important it is for SMEs to keep records, little research has looked at how subjective views of accounting practises are linked to performance. To do this, the research analyses 370 SMEs using Spearman’s correlation, Independent Samples t-test and Multiple Linear Regression. The data shows that there is a noticeable but not major connexion between how useful SMEs find accounting practises and their performance. SMEs that believed in the advantages of social media did better. The amount of record-keeping, as seen by regular entries, software use, financial review and accountant involvement, explained 37.5% of the differences in performance. Most other studies centre on technical or compliance issues, but this study emphasises how SMEs’ financial actions and views affect their success. These results suggest that policymakers, SME support agencies and entrepreneurs should promote financial literacy, make accounting easier and create environments that support the growth of SMEs.